2007
DOI: 10.1007/s11524-007-9160-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrated Trauma Treatment on Outcomes in a Racially/Ethnically Diverse Sample of Women in Urban Community-based Substance Abuse Treatment

Abstract: This study presents findings from a quasiexperimental, nonequivalent, group-design study with repeated measures that explored the effects of integrated trauma-informed services on the severity of substance abuse, mental health, posttraumatic stress disorder (PTSD) symptomatology among women with histories of trauma in urban, community-based substance abuse treatment. The study also explored if the model of integrated services was equally beneficial for women of various racial/ethnic groups. Participants in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 44 publications
4
66
1
Order By: Relevance
“…Substance abuse and mental health symptoms improve with increased time in treatment in interaction with more severe baseline symptoms. These findings lend support to a growing consensus that for persons with co-occurring disorders, an integrated treatment approach is the most appropriatẽ Amaro et al, 2007a;Amaro et al, 2007b;Barrowclough, et al, 2001;Cocozza et al, 2005;Hellerstein et al, 2001;Morrissey, Jackson et al, 2005;Ouimette et al, 1998;RachBeisel et al, 1999;Ziedonis & Stern, 2001!. …”
Section: Note For Tables 3 4 Andsupporting
confidence: 66%
“…Substance abuse and mental health symptoms improve with increased time in treatment in interaction with more severe baseline symptoms. These findings lend support to a growing consensus that for persons with co-occurring disorders, an integrated treatment approach is the most appropriatẽ Amaro et al, 2007a;Amaro et al, 2007b;Barrowclough, et al, 2001;Cocozza et al, 2005;Hellerstein et al, 2001;Morrissey, Jackson et al, 2005;Ouimette et al, 1998;RachBeisel et al, 1999;Ziedonis & Stern, 2001!. …”
Section: Note For Tables 3 4 Andsupporting
confidence: 66%
“…General interventions for PTSD in primary care settings include medication, short-term psychotherapy, and referral to psychiatric clinics, 52,53 yet urban women may have unique needs. Social support, 54 spiritual well-being, 55 and integrated treatment for alcohol and drug abuse 56,57 have been identified as needs of traumatized urban women. Integrating these or other unique needs may improve treatment of PTSD in urban women.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings from the multisite Women, Co-Occurring Disorders and Violence Study~WCDVS!, sponsored by the Substance Abuse and Mental Health Services Administration~SAMHSA!, have demonstrated that integrated services for women with co-occurring substance abuse and mental health disorders and a history of trauma increase treatment retention~Amaro, Chernoff, Brown, Arévalo, &Gatz, 2007! andimprove treatment outcomes~Amaro, Dai, Arévalo, Acevedo, Matsumoto, &Nieves, 2007;Cocozza et al, 2005;Finkelstein, Mazelis, Brown, Jackson, & Banks, 2005;Morrissey, Jackson, et al, 2005!. A remaining question is whether integrated services that include trauma treatment are also effective in reducing sexual risk behaviors in this population of women.…”
mentioning
confidence: 99%